Smart Financial Management Strategies for Enhancing the Profitability of Micro, Small, and Medium Enterprises in the Era of Global Competition - Dede Supian; Junaedi Junaedi; Syaifuddin Syaifuddin (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objective: Digital transformation in the financial sector provides strategic opportunities for Micro, Small, and Medium Enterprises (MSMEs) to improve efficiency, access to finance, and competitiveness. However, many MSMEs have not fully optimized these opportunities due to limited financial management capability and uneven adoption of financial technology. This study aims to analyze the effect of smart financial management strategies on MSME profitability, both directly and indirectly through financial technology adoption.Methodology: This study employed a quantitative explanatory research design. The population consisted of active MSMEs in West Java Province that had used at least one form of financial technology service. The sample was selected using purposive sampling, involving 200 MSME owners or managers as respondents. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.Findings: The results show that smart financial management strategies have a positive and significant effect on MSME profitability and financial technology adoption. Financial technology adoption also has a positive and significant effect on MSME profitability. Furthermore, financial technology adoption partially mediates the relationship between smart financial management strategies and MSME profitability. These findings indicate that financial management capability improves profitability not only through direct financial efficiency, but also by encouraging the effective adoption and utilization of digital financial services.Conclusion: This study highlights the importance of integrating internal financial management capability with financial technology adoption as a strategic approach to improving MSME profitability. Theoretically, this study contributes to the fintech and strategic financial management literature by integrating the Resource-Based View and the Technology Acceptance Model in explaining MSME performance. Practically, the findings suggest that MSME development programs should combine financial management training, digital financial literacy, and fintech adoption assistance to strengthen business sustainability and competitiveness.